Advanced Material Models for Stamping of AW 5754 Aluminum Alloy - Slota, J.; Šiser, M. (Проблемы прочности, 2016)
Predictions by numerical simulations are strongly influenced by availability and reliability of input data. In the most used computational models, the material behavior during deformation is described only by static tensile test in combination with Lankford coefficients of anisotropy. However, for some specific materials like highly anisotropic aluminum alloys, such description of material behavior is insufficient and, in many cases, the calculated results are not in good agreement with the measured ones. In this paper, the implementation of advanced material model for deep-drawing process to explicit FE code and the procedure of measurement of the most important input material data for calculations on the aluminum alloy AW 5754 are discussed. Results of the numerical simulation are compared with the experimental ones and exhibit a close correlation.